Patient-centered mobile health data management solution for the German health care system (the DataBox project) - Brinker, Titus Josef; Kalle, Christof von (JMIR cancer)
This article describes the DataBox project which offers a perspective of a new health data management solution in Germany. DataBox was initially conceptualized as a repository of individual lung cancer patient data (structured and unstructured). The patient is the owner of the data and is able to share his or her data with different stakeholders. Data is transferred, displayed, and stored online, but not archived. In the long run, the project aims at replacing the conventional method of paper- and storage-device-based handling of data for all patients in Germany, leading to better organization and availability of data which reduces duplicate diagnostic procedures, treatment errors, and enables the training as well as usage of artificial intelligence algorithms on large datasets. [JMIR Cancer 2018;4(1):e10160]
Gesehen am 08.10.2019